2008
DOI: 10.1523/jneurosci.5349-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin Enhances AMPA and NMDA Receptor Activity in Spinal Cord Dorsal Horn Neurons by Activating Multiple Kinases to Produce Pain Hypersensitivity

Abstract: -1). Extracellular signal-regulated kinase (ERK) activation is involved after the PKC and PKA coactivation, and intrathecal administration of bradykinin induces a thermal hyperalgesia in vivo, which is reduced by inhibition of ERK, PKA, and PKC. We conclude that bradykinin, by activating multiple kinases in dorsal horn neurons, potentiates glutamatergic synaptic transmission to produce pain hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
91
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 45 publications
6
91
0
Order By: Relevance
“…PLA 2 initiates the release of arachidonic acid which is converted to PGE2, by cyclooxygenase (Cox) and prostaglandin synthases, and can activate PKA via E-prostanoid G-protein coupled receptors (Smith et al, 2000). PKA and PKC may phosphorylate NMDA or AMPA receptor subunits, changing the membrane traffic and their kinetic properties (voltage-dependent block, channel open time, burst behavior), triggering an increase in synaptic effectiveness (Kohno et al, 2008). Very recently, it was shown that B2R stimulation leads to neuroprotection after NMDA excitotoxicity in the CA1 area of rat hippocampal slices via phosphatidylinositol 3-kinase and not by MEK/MAPK signaling (Martins et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…PLA 2 initiates the release of arachidonic acid which is converted to PGE2, by cyclooxygenase (Cox) and prostaglandin synthases, and can activate PKA via E-prostanoid G-protein coupled receptors (Smith et al, 2000). PKA and PKC may phosphorylate NMDA or AMPA receptor subunits, changing the membrane traffic and their kinetic properties (voltage-dependent block, channel open time, burst behavior), triggering an increase in synaptic effectiveness (Kohno et al, 2008). Very recently, it was shown that B2R stimulation leads to neuroprotection after NMDA excitotoxicity in the CA1 area of rat hippocampal slices via phosphatidylinositol 3-kinase and not by MEK/MAPK signaling (Martins et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Once activated, ERK can regulate the phosphorylation of many membrane receptors and the expression of many genes, resulting in short- and long-term functional changes in the spinal nociception process [31,32]. For example, ERK activation has been demonstrated to regulate the expression of several pain-related genes including COX-2, neurokinin 1 and tyrosine receptor kinase B [33].…”
Section: Discussionmentioning
confidence: 99%
“…In many pain models, PKC has been found to be necessary for maintaining central sensitization and directly affects molecular signaling pathways mediating central sensitization in pain. Activation of PKC results in the direct activation of intracellular signaling molecules of the mitogenactivated protein kinase (MAPK) family that are critically involved in pain sensitization, including extracellular-signal-related kinase (ERK) 1 and 2, p38, and stress-activated protein kinase (SAPK)/ c-Jun N-terminal kinase (JNK) [4,22,23]. In addition, PKC γ has also been reported to phosphorylate NMDA receptors [24] and promote the trafficking of NMDA receptors to the cell membrane [25].…”
Section: Discussionmentioning
confidence: 99%